ANALYSIS OF FLOOD WATER SURFACE ELEVATION CONTROL IN THE CINAMBO SUB-WATERSHED, GEDEBAGE MARKET AREA, BANDUNG CITY - Huwaida Hasari, Sarah
Flooding is a natural phenomenon that has a significant impact on urban areas and communities. One area that frequently experiences flooding is the Cinambo River Basin, particularly in the Pasar Gedebage area of Bandung City. This study aims to propose solutions to reduce flood water surface elevation in the region. A hydrological analysis was conducted to obtain the 5-year return period design discharge using the Synthetic Unit Hydrograph (SUH) SCS method, processed through HEC-HMS. A hydraulic analysis was then performed using HEC-RAS to simulate water inundation during floods and to design flood control structures. The proposed solutions include river normalization and the construction of parapet levees along the riverbanks, with an additional alternative of a retention pond. Stability checks were conducted, and it was found that the design meets the minimum safety factor requirements. The total cost for the proposed flood control plan in the study area is Rp7,808,761,000.00.